A novel soil quality assessment method for sustainable soil management and enhancing crop productivity in tribal areas of central India - Rajendiran S. Selladurai; Mohan Lal Dotaniya; M Vassanda Coumar; Samaresh Kundu; Nishant Kumar Sinha; A.K. Tripathi; Sanjay Srivastava; J.K. Saha; A.K. Patra (Environment Conservation Journal, 2021)
Soil quality degradation is a major threat to any agricultural production system. Therefore periodical monitoring of soil quality status is inevitable for sustainable management of agricultural production systems. Though there are various methods available to assess the soil quality, simple and management oriented methods are necessary. The current investigation aimed to evaluate soil quality of tribal areas of central India adopting minimum dataset of 15 soil physical, chemical and biological parameters. A novel scoring technique was followed to score soil quality indicators based on its relation with crop yield, degree of variation and percent deficiency. Relative soil quality index (RSQI) was calculated and was correlated with crop productivity. Most of the soils in the region had poor soil quality (77.2% in Jhabua, 85.4% in Alirajpur and 67.2% in Dhar) with low crop yield. The major constraints of crop production in these areas were low soil organic carbon (<0.5%), available N (<280 kg ha-1), S (<10 mg kg-1), P (<10 kg ha-1), Zn (<0.5 mg kg-1), dehydogenase activity (10 ?g TPF g-1 24 h-1) and soil depth (<1 m). Adopting sustainable management practices could improve soil quality and crop productivity. This new approach is simple and systematic; this principle can be easily adoptable to other locations, and principally focuses on management related and soil parameters that constraint to production and ecological functions.